On the performance of non-coherent transmission schemes with equal-gain combining in correlated generalized K-fading - Zhu, Cindy; Mietzner, Jan; Schober, Robert (IEEE Vehicular Technology Conference, 2009)
The generalized K-fading model, characterized by two parameters, k and m, was recently shown to accurately capture the effects of composite shadowing and multipath fading in wireless communication systems. In this paper, we derive closed-form expressions for the bit error probability of two non-coherent transmission schemes over L diversity branches being subject to generalized K-fading. Specifically, focus is on binary differential phase-shift keying (DPSK) and binary non-coherent frequency-shift keying (FSK) modulation with equal-gain combining at the receiver. We also derive expressions for the asymptotic diversity order, which reveal an interesting interplay between the two fading parameters k and m. Moreover, we show that the diversity order of the considered non-coherent transmission schemes is the same as in the case of coherent transmission. Finally, numerical performance results are presented, and our analytical results are corroborated by means of Monte-Carlo simulations. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03